Sinkretisme Keagamaan: Din Ilahi Sultan Jalaluddin Akbar Sebagai Media Toleransi dan Politik Dinasti Mughal 1560-1605 - Yuda, Mas Rangga; Wahyudi, Deny Yudo (NALAR, 2022)
Sultan Jalaluddin Akbar the ruler of the Mughals had the concept of Din Ilahi as a form of religious syncretism. Din Ilahi is a teaching of tolerance and religious pluralism which requires all religions to unite under its leadership. However, the concept of the Din Ilahi received a lot of criticism and challenges from Islamic circles, especially in the palace sphere. This article aims to briefly overview religious syncretism with the concept of Din Ilahi from Sultan Jalaluddin Akbar. This article also tries to portray how the concept of the Din Ilahi as a syncretistic thought has received a lot of criticism and challenges from Islamic circles. The method used is the historical research method or Historical Research which consists of four stages. These stages are heuristics, source criticism, interpretation, and historiography. The result found is that the Din Ilahi is not only a religious syncretism but also a political tool of Sultan Akbar in uniting every difference of belief in the Mughal Dynasty. The Din Ilahi in its teachings makes the majority of Muslims discriminated against. The Din Ilahi is considered to have harmed the actual teachings of Islam by mixing various religious teachings.KeywordsSultan Akbar;